The Role of Children in Women’s Marital Satisfaction in Tehran, 2016 - Darooneh, Tayebeh; Hajizadeh Bandeghara, Fahimeh; Saei Ghare naz, Marzieh; Kholosi, Farnaz; Nasiri, Malihe; Ozgoli, Giti (Advances in Nursing & Midwifery, 2020)
Introduction: One of the important factors affecting women’s satisfaction with their marital life and the stability of family foundation is children. Several studies on the impact of the number and gender of children on marital satisfaction have shown conflicting results. This study is intended to explore the role of children on women’s marital satisfaction. Methods: This cross-sectional study was conducted on 264 married women living in Tehran. Data collection tool was a two-part questionnaire containing demographic information and the modified version of Enrich marital satisfaction scale. Data analyzed by SPSS software, version 17. Indeed, Chi-square, Mann-Whitney and Kolmogorov- Smirnov tests and linear regression were employed. Significance level was taken 0.05. Results: The results suggested that mean ± standard deviation [1] of marital satisfaction score for all research units was 37.28 ± 6.24. Generally, the average score of marital satisfaction for women without any children was higher compared to those with one or two children. Moreover, women whose first child was a girl had a higher average score in marital satisfaction than those whose first child was a boy. According to the results of multiple linear regression model, a significant predictor of women’s marital satisfaction was the gender of the first baby (P = 0.01). Conclusions: The results demonstrated that generally women with no child had higher marital satisfaction and the gender of the child in our research community played a determinant role in their marital satisfaction. Analytical studies in which the intervening variables are controlled are recommended.